Photoisomerization, energy storage, and charge separation: A model for light energy transduction in visual pigments and bacteriorhodopsin - Honig, B. (1979)
A simple model for the early events in visual pigments and bacteriorhodopsin is proposed. The model makes use of the likelihood that a negatively charged amino acid forms a salt bridge with the positively charged nitrogen of the retinylic chromophore. The photochemical event is a cis-trans isomerization in visual pigments and a trans-cis isomerization in bacteriorhodopsin, which in each case cleaves the salt bridge and thus separates charge in the interior of the protein. We propose that this is how the energy of a photon is transduced into chemical free energy of the primary photoproduct. The use of photoisomerization of a flexible chromophore to achieve charge separation provides a general mechanism which may be applicable to other systems. Our model explains many of the fundamental properties of visual pigments and their photoproducts. First, the extraordinarily low rate of thermally populating the ground state of the primary photoproduct, as determined from psychophysical and electrophysiological measurements, is seen as resulting from the large barrier to thermal isomerization about a double bond, perhaps enhanced by electrostatic attraction in the salt bridge. Second, the increase in energy and the spectral red shift that characterize the primary photochemical events are natural consequences of the separation of charge. Proton-dependent processes detected with picosecond techniques are proposed to be ground-state relaxation processes following the primary photochemical event. Finally, the charged groups of the salt bridge, repositioned by photoisomerization, provide a simple mechanism for vectorial proton translocation in bacteriorhodopsin.